Enhancing EFL learners’ language development through collaborative tasks - Baharun H.; Zakaria A.R. (American Scientific Publishers, 2024)
This paper reports on a study that investigates the use of collaborative tasks to elicit Language Related Episodes (LREs) during learners’ oral interaction. The study examines the frequency and nature of LREs generated by the participants during interaction in EFL speaking class. Nine language learners in groups of three participated in the study. They were instructed to complete two collaborative task types during which their performance was recorded. A qualitative analysis of the data revealed that the learners produced LREs during task completion for both tasks. The results obtained indicate that lexical LREs tend to be more frequent than other types of LREs in the interactions. The lexical LREs produced may create opportunities for language development among the EFL learners. Results of the study were discussed in light of pedagogical implications in a language classroom.